Maintenance Decision Support Model for Railway Track Geometry Maintenance Planning Using Cost, Reliability, and Availability Factors: A Case Study. Issue 7 (July 2022) - Kasraei, Ahmad; Ali Zakeri, Jabbar
Determining the strategy and planning for maintenance operations on railway tracks is important given the increasing demand from both freight and passengers. An important prerequisite of maintenance planning is the ability to predict the overall and geometric conditions of the railway in the near future. It is, therefore, necessary to develop a degradation model and consider the effect of various maintenance operations using a recovery model. According to EN 13848-5, the alert limit (AL) can be used as an indicator to plan maintenance operations. The current paper benefits from this index as well as the effect of its changes on important parameters such as maintenance costs, availability, and reliability to present a maintenance decision support model. This model allows infrastructure managers to plan maintenance interventions under the conditions of their intended usage strategy. The results of this paper indicate that choosing suitable AL could affect total maintenance cost and availability by up to 57% and 33% respectively.